Intraindividual Effects of Take-Off Distance on Hurdling and Interval Running in Sprint Hurdles - Keitaro Seki; Shota Kikuchi; Kunihiro Okamura; Ayata Kageyama; Giorgos Paradisis (Biomechanics)
Purpose: This study explores the impact of take-off distance on hurdling and interval running kinematics in sprint hurdles, recognizing its potential to improve performance. While beginners often use shorter take-off distances, a deeper understanding could inform coaching strategies aimed at improving hurdle technique. Methods: Ten male elite and highly trained hurdlers ran 60 m hurdles under original, short, and long take-off distances (OTD, STD, and LTD, respectively). The sagittal plane kinematics of the fourth hurdle and interval running were obtained using two high-speed cameras at a rate of 120 frames per second. Intraindividual step parameters were compared between conditions. Results: Running speed and step frequency were significantly lower in the STD than in the OTD and LTD. Significant interactions were found for step length with a significantly longer recovery step length in the STD than in the LTD. Furthermore, the hurdling distance was significantly longer in the LTD than in the OTD. In addition, the touchdown distance was significantly shorter in the LTD and longer in the STD compared to the OTD. Therefore, an STD is associated with a shorter acceleration distance between hurdles, whereas an LTD is associated with a longer acceleration distance. Therefore, the take-off distance influenced the distance for acceleration between hurdles, and the recovery step was related to the take-off distance. Conclusions: STD has negative effects on hurdling and interval running, even among elite and highly trained hurdlers.